2020
DOI: 10.1371/journal.ppat.1008464
|View full text |Cite
|
Sign up to set email alerts
|

The B-cell inhibitory receptor CD22 is a major factor in host resistance to Streptococcus pneumoniae infection

Abstract: Streptococcus pneumoniae is a major human pathogen, causing pneumonia and sepsis. Genetic components strongly influence host responses to pneumococcal infections, but the responsible loci are unknown. We have previously identified a locus on mouse chromosome 7 from a susceptible mouse strain, CBA/Ca, to be crucial for pneumococcal infection. Here we identify a responsible gene, Cd22, which carries a point mutation in the CBA/Ca strain, leading to loss of CD22 on B cells. CBA/Ca mice and gene-targeted CD22-defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…This observation is consistent with the results of this study (Salem et al, 2007). For another example, B-cell receptor CD22 (Cd22) can mediate the interaction between B cells, participate in the localization of B cells in lymphoid tissues, and play a regulatory role in signal transduction between antigen and receptor during the immune response (Fernandes et al, 2020). It downregulation indicates that the ability of blood coagulation is decreased (Wang et al, 2021).…”
Section: Regulation Of the Immunesupporting
confidence: 89%
“…This observation is consistent with the results of this study (Salem et al, 2007). For another example, B-cell receptor CD22 (Cd22) can mediate the interaction between B cells, participate in the localization of B cells in lymphoid tissues, and play a regulatory role in signal transduction between antigen and receptor during the immune response (Fernandes et al, 2020). It downregulation indicates that the ability of blood coagulation is decreased (Wang et al, 2021).…”
Section: Regulation Of the Immunesupporting
confidence: 89%
“…Here, its downregulation indicated, in a sense, a decline in coagulation ability. B-cell receptor CD22 ( CD22 ) can mediate the interaction between B cells, participate in the localization of B cells in lymphoid tissues, and play an important regulatory role in signal transduction between antigen and receptor during the immune response ( 73 ). Research on the influence of starvation on zebrafish liver also indicated the downregulation of CD22 ( 17 ), which is consistent with the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, for Rpsa, changes were only observed for strain TIGR4, with down-regulation in TIGR4-infected blood, and up-regulation in TIGR4-infected kidneys. Another receptor, found in B cells (CD22), was shown to be important for host resistance to the pneumococcus ( 56 ). It was consistently down-regulated in all our infected blood samples but not at other sites, leaving the host susceptible to further infection, and possibly explaining the high titers of Spn we observed in the blood.…”
Section: Discussionmentioning
confidence: 99%